2021
DOI: 10.3390/nu13113797
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Algorithms to Predict Resting Energy Expenditure in Critically Ill Children

Abstract: Introduction: Accurate assessment of resting energy expenditure (REE) can guide optimal nutritional prescription in critically ill children. Indirect calorimetry (IC) is the gold standard for REE measurement, but its use is limited. Alternatively, REE estimates by predictive equations/formulae are often inaccurate. Recently, predicting REE with artificial neural networks (ANN) was found to be accurate in healthy children. We aimed to investigate the role of ANN in predicting REE in critically ill children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 22 publications
3
12
0
1
Order By: Relevance
“…One study found a positive association between age and EE. 34 A recent study also observed a positive association between EE and the presence of multiorgan failure, but the causes of PICU admission and underlying disease were not correlated with EE. 35 The systematic review 5 and three recent studies 32,35,37 showed no correlation between the disease severity and EE.…”
Section: Methods Of Estimation Of Ree (Subquestion 1b)mentioning
confidence: 94%
See 3 more Smart Citations
“…One study found a positive association between age and EE. 34 A recent study also observed a positive association between EE and the presence of multiorgan failure, but the causes of PICU admission and underlying disease were not correlated with EE. 35 The systematic review 5 and three recent studies 32,35,37 showed no correlation between the disease severity and EE.…”
Section: Methods Of Estimation Of Ree (Subquestion 1b)mentioning
confidence: 94%
“…Most studies 13,35–37,39 observed that the Schofield equation, which predicted REE within ±10% of the measured REE in 30%–38% of observations only, 13,37 was one of the least inaccurate. The direction of accuracy differed among studies, with underestimation and overestimation of REE, 13,37 mainly an underestimation, 35,46 or an overestimation 31,34,36 . One study 39 showed that the bias of the Schofield equation differed along the REE range of values, resulting in the underestimation of REE in young children and the overestimation in older children, which may explain these differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current guidelines suggest evaluating patients with suspected hypometabolism or hypermetabolism such as patients with a neurologic or oncologic diagnosis [9]. However, given the current limited applicability in the use of indirect calorimetry in large numbers of patients, the exploration into novel methods of measuring energy expenditure remains a high priority [10,11].…”
Section: Metabolism and Metabolic Monitoringmentioning
confidence: 99%